Moral Judgments & International Crimes: The Disutility of Desert - Woods, Andrew Keane (2012)
The international criminal regime exhibits many retributive features, but scholars and practitioners rarely defend the regime in purely retributive terms—that is, by reference to the inherent value of punishing the guilty. Instead, they defend it on the consequentialist grounds that it produces the best policy outcomes, such as deterrence, conflict resolution, and reconciliation. These scholars and practitioners implicitly adopt a behavioral theory known as the utility of desert, a theory about the usefulness of appealing to people's retributive intuitions. That theory has been critically examined in domestic criminal scholarship but practically ignored in international criminal law. This Article fills this gap and argues that whatever its merits in the domestic realm, there are special reasons to be skeptical about the utility of desert claim in the international context. Moral intuitions as heuristics for moral judgments are error-prone, and the international criminal regime has a number of extraordinary features that may increase the likelihood and cost of these errors. These features include the complexity of the crimes; the diversity of stakeholders who possess heterogeneous intuitions; and the regime's multiple goals, some of which may be inhibited by moral condemnation. After examining these differences, the Article outlines the implications of the analysis for regime design. Some of these design implications accommodate the international criminal regime's current retributive approach, and some are fundamentally incompatible with retributivism